2009
DOI: 10.1016/j.jacc.2009.05.070
|View full text |Cite
|
Sign up to set email alerts
|

High Central Pulse Pressure Is Independently Associated With Adverse Cardiovascular Outcome

Abstract: Objective To facilitate clinical use of central PP, we sought to determine a value that might predict adverse outcome and thereby provide a target for assessment of intervention strategies. Background We previously documented that central pulse pressure (PP) more strongly relates to carotid hypertrophy and extent of atherosclerosis and, more importantly, better predicts incident cardiovascular disease (CVD) than brachial PP. Methods Radial applanation tonometry was performed in the 3rd Strong Heart Study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
155
0
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(176 citation statements)
references
References 19 publications
5
155
0
16
Order By: Relevance
“…16,17 The arterial pulse wave is generated by the sum of the forward pressure wave, timing of the reflected wave and the magnitude of the reflected wave along the arterial tree. 18 Arterial wave reflection occurs in the peripheral arteries due to changes in the arterial properties or in the architecture of the arterial tree.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The arterial pulse wave is generated by the sum of the forward pressure wave, timing of the reflected wave and the magnitude of the reflected wave along the arterial tree. 18 Arterial wave reflection occurs in the peripheral arteries due to changes in the arterial properties or in the architecture of the arterial tree.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Therefore, measurement of central blood pressure is increasingly used in epidemiological studies. Another important aspect of central blood pressure measurement is that antihypertensive drugs have differential effects on central pressure despite similar effects on brachial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent studies have suggested that central aortic BP may be better associated with target organ damage and clinical outcomes in people with hypertension. [3][4][5][6][7] Moreover, in Marfan's disease, it has been previously shown that central blood pressure (cBP) has a key role in the pathogenesis of aortic aneurysms. 8 In hypertensive patients, the ARD, and in particular dilatation of the sinus of Valsalva, is associated with more pronounced alterations in cardiac structure and geometry than in normotensive subjects; 2 however, the relationship between aortic root size and both the central and the peripheral BP levels has not yet been fully investigated in patients with hypertension and aortic dilatation.…”
Section: Introductionmentioning
confidence: 99%